The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1051/0004-6361:20054057
|View full text |Cite
|
Sign up to set email alerts
|

New galactic open cluster candidates from DSS and 2MASS imagery

Abstract: An inspection of the DSS and 2MASS images of selected Milky Way regions has led to the discovery of 66 stellar groupings whose morphologies, color-magnitude diagrams, and stellar density distributions suggest that these objects are possible open clusters that do not yet appear to be listed in any catalogue. For 24 of these groupings, which we consider to be the most likely to be candidates, we provide extensive descriptions on the basis of 2MASS photometry and their visual impression on DSS and 2MASS. Of these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
135
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(142 citation statements)
references
References 36 publications
6
135
1
Order By: Relevance
“…Robitaille et al (2008), Evans et al (2009), andGutermuth et al (2010) used Spitzer data to classify > 13 × 10 3 YSOs. Borissova et al (2011) discovered 96 candidate clusters 2 in the VVV survey (Minniti et al 2010), while Mercer et al (2005) identified 92 star clusters via GLIMPSE data (see also Froebrich et al 2007;Kronberger et al 2006). Those infrared surveys resolved numerous individual cluster stars, and in many instances confirmed existing evidence of star formation put forth by low-resolution surveys (e.g., IRAS and maser observations, Avedisova 2002).…”
Section: Introductionmentioning
confidence: 66%
“…Robitaille et al (2008), Evans et al (2009), andGutermuth et al (2010) used Spitzer data to classify > 13 × 10 3 YSOs. Borissova et al (2011) discovered 96 candidate clusters 2 in the VVV survey (Minniti et al 2010), while Mercer et al (2005) identified 92 star clusters via GLIMPSE data (see also Froebrich et al 2007;Kronberger et al 2006). Those infrared surveys resolved numerous individual cluster stars, and in many instances confirmed existing evidence of star formation put forth by low-resolution surveys (e.g., IRAS and maser observations, Avedisova 2002).…”
Section: Introductionmentioning
confidence: 66%
“…IPHASXJ194040.3+293010. Classified as a possible PN by Roman et al (2000) and as a PN by Kronberger et al (2006) but no spectroscopic confirmation is available and hardly visible in the IPHAS continuum filters. Possibly a round PN.…”
Section: Candidates Classified In Simbadmentioning
confidence: 99%
“…IPHASXJ194226.1+214522. Classified as a possible PN (Kronberger et al 2006) but no spectroscopic confirmation is available. Possibly a bipolar/quadrupolar PN.…”
Section: Candidates Classified In Simbadmentioning
confidence: 99%
See 1 more Smart Citation
“…The first consists of targeted searches around known IR and radio sources, or in areas of interest (e.g., the Galactic bulge or known nearby star-forming regions; i.e., Dutra & Bica 2000; Kronberger et al 2006). The second is unbiased: it is based on automated techniques that apply sets of objective rules to identify overdensities in flux or stellar surface-number density in the pixel data or in the point-source catalogs, respectively.…”
Section: Introductionmentioning
confidence: 99%